Analisis Penerapan Metode Activity Based Costing (ABC) Dalam Menentukan Harga Pokok Produksi (Studi Kasus : Bread Islamy Rantauprapat) - Natasya, Tifani; Sudiarti, Sri; Ahmad Hasibuan, Nur Fadhilah (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Activity based costing method is the accounting method used to calculate the cost of production which calculates activity-based costs. Calculation of activity based costing can be done by adding up all detailed production costs divided by the number of production units. The purpose of this study is to find out how the method of calculating the cost of goods manufactured is applied by the company and to find out whether the method applied by the company is in accordance with the activity based costing method. The object of this research is Bread Islamy Rantauprapat which is located at Jalan Sirandorung No. 144 b-c Padang Bulan Rantauprapat. The method used in this study is a qualitative method by describing and disclosing facts and conditions in the field clearly. The results of the study concluded that Bread Islamy Rantauprapat applied traditional cost accounting methods in determining the cost of production. And Bread Islamy Rantauprapat has not applied the activity based costing method in determining the cost of production.